Fatigue properties and fracture mechanism of load carrying type fillet joints with one-sided welding - Takamasa Abe; Hiroyuki Akebono; Masahiko Kato; Atsushi Sugeta (Fracture and Structural Integrity)
The structures of the hydraulic excavator and the crane have numerous one-sided welded joints. However, attachments with box like structures are difficult to weld at both sides. Therefore, high accurate evaluation method is needed. In this study, the fatigue properties and the fracture mechanism of the load carrying type fillet joints with one-sided welding were investigated experimentally to evaluate its fatigue damage with high accuracy based on the experimental results. As the results, fatigue cracks in the test piece initiated from the tip of the unwelded portion and propagated into the welding materials. Multiple welding defects were observed in the unwelded portion, but did not appear to be crack origins. Although these welding defects affected the direction of crack propagation they exerted minimal influence. The three-dimensional observations revealed that fatigue cracks initiate at an early stage of the fatigue development. We infer that the fatigue lifetime is chiefly governed by the crack propagation lifetime. Cracks were initiated at multiple sites in the test piece. As the number of cycles increased, these cracks propagated and combined. So considering the combination of cracks from multiple crack origins is important for a precise evaluation of fatigue damage.